2012
DOI: 10.1155/2012/132931
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Activation of Nrf2 Protects Human Coronary Artery Endothelial Cells against an Oxidative Challenge

Abstract: Activation of NF-E2-related factor 2 (Nrf2) is a potential therapeutic intervention against endothelial cell oxidative stress and associated vascular disease. We hypothesized that treatment with the phytochemicals in the patented dietary supplement Protandim would induce Nrf2 nuclear localization and phase II antioxidant enzyme protein in human coronary artery endothelial cells (HCAECs), protecting against an oxidant challenge in an Nrf2- dependent manner. Protandim treatment induced Nrf2 nuclear localization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
6
39
0
Order By: Relevance
“…Furthermore, among the antioxidant and detoxification enzymes, Heme oxygenase-1 (HO-1) and glutamate-Lcysteine ligase catalytic subunit (GCLC) are the most important. Recent studies have shown that activation of Nrf2 plays an important role in acute liver injury both in vitro and in vivo (7,8). To date, multiple signaling kinases have been reported to regulate Nrf2, including mitogen-activated protein kinase (MAPK), protein kinase C (PKC) and phosphatidylinositol-3-kinase (PI3K) (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among the antioxidant and detoxification enzymes, Heme oxygenase-1 (HO-1) and glutamate-Lcysteine ligase catalytic subunit (GCLC) are the most important. Recent studies have shown that activation of Nrf2 plays an important role in acute liver injury both in vitro and in vivo (7,8). To date, multiple signaling kinases have been reported to regulate Nrf2, including mitogen-activated protein kinase (MAPK), protein kinase C (PKC) and phosphatidylinositol-3-kinase (PI3K) (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these phytochemicals are most appropriate in protecting oxidative stress-related damages due to their tendency to exert better protective effect without any distinct side effect (Donovan et al, 2012). As a naturally occurring plant phenol, 6-gingerol has antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The most common outcome of oxidative stress is the increased damage of lipid, DNA and proteins that resulted in the development of different pathologies (Donovan et al, 2012). The aim of this study was to investigate the possibility that 6-gingerol may inhibit the oxidative DNA damage of hydrogen peroxide in human umbilical vein endothelia cells (HUVECs).…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 promotes cell survival by binding the antioxidant response element (ARE) in the promoter of downstream target genes that promote detoxification of xenobiotics and scavenging of reactive oxygen species (ROS). The benefit of Nrf2 activation has been demonstrated in various pathological states such as diabetes, chemoprevention, and cardiovascular and neurological diseases [15]. …”
Section: Introductionmentioning
confidence: 99%